1984
DOI: 10.1111/j.1476-5381.1984.tb10776.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective antinociceptive effects of tizanidine (DS 103–282), a centrally acting muscle relaxant, on dorsal horn neurones in the feline spinal cord

Abstract: The effects of the centrally acting muscle relaxant tizanidine have been examined on the responses of laminae IV and V dorsal horn neurones to peripheral noxious and non-noxious stimuli in cats spinalized at Ll. 2 lontophoretic ejection of tizanidine near the cell bodies of the recorded neurones or more dorsally into laminae 11-HI resulted in a marked and prolonged depression of excitation of laminae IV and V neurones evoked by noxious stimuli. Spontaneous firing was also depressed in many neurones but respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The first studies on this drug were carried out in beginning of 1980s, when the site and the mechanism of the antinociceptive action were still not known. 121,122 A few years later it was observed that the analgesic effect induced by tizanidine in the tail-flick test in mice was antagonized by the a 2 -adrenoceptor antagonist yohimbine, suggesting that the analgesia could be mediated by a 2 -adrenoceptors. 123 Asano and coworkers demonstrated that there is a good correlation between antinociceptive effect and binding affinity for tizanidine in the spinal cord and brain.…”
Section: Tizanidinementioning
confidence: 97%
“…The first studies on this drug were carried out in beginning of 1980s, when the site and the mechanism of the antinociceptive action were still not known. 121,122 A few years later it was observed that the analgesic effect induced by tizanidine in the tail-flick test in mice was antagonized by the a 2 -adrenoceptor antagonist yohimbine, suggesting that the analgesia could be mediated by a 2 -adrenoceptors. 123 Asano and coworkers demonstrated that there is a good correlation between antinociceptive effect and binding affinity for tizanidine in the spinal cord and brain.…”
Section: Tizanidinementioning
confidence: 97%
“…97,98 These findings have been bolstered by the observation that tizanidine has an antinociceptive effect in animal models. [99][100][101] Finally, tizanidine enhances vibratory inhibition of H reflex in humans and reduces abnormal co-contraction, effects which have been correlated with clinical improvements of spasticity in patients. 102…”
Section: Physiology Of Actionmentioning
confidence: 98%
“…In addition to its muscle relaxant action, tizanidine has an antinociceptive activity which is stronger than that of morphine and mediated by a non-opioid mechanism (Davies and Johnston, 1984; Kameyama et a/., 1985; Kameyama et al, 1986;Nabeshima et al, 1986). Recent studies have also demonstrated anticonvulsant properties of tizanidine in rodent and primate models of epilepsy (De Sarro et a/., 1984).…”
Section: Introductionmentioning
confidence: 99%